A national cross-sectional study on the influencing factors of low HPV vaccination coverage in mainland China - Yin, Xiangju; Zhang, Mengrui; Wang, Fei; Huang, Yue; Niu, Yuyao; Ge, Pu; Yu, Wenli; Wu, Yibo (Frontiers in Public Health, 2023)
Cervical cancer is by far the most common HPV-related disease, which nearly all cases of cervical cancer can be traced to HPV infection. In this study，we showed in addition to age, the place of residence, capita household income/month, individual self-efficacy and family health literacy have significant effects on HPV vaccination rates. The association strength between NGSES and HPV vaccination rates is statistically significant and non-linear; Also, the association strength between FHS-SF and the HPV vaccination rate is statistically significant and non-linear. This study will help to promote the vaccination of the HPV vaccine and provide a scientific basis for cervical cancer prevention.